1996
DOI: 10.1093/gerona/51a.2.m64
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Gait Patterns in Older Women: A Randomized Controlled Trial

Abstract: These findings show that exercise can increase gait velocity and related parameters in older persons, and that part of this increase may be mediated by improved lower limb muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
2
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 0 publications
5
85
2
9
Order By: Relevance
“…The effects of exercise on lower extremity muscle strength and these age-related gait changes have been reported for adults aged 60 years and older (Buchner et al, 1997;Lord et al, 1996). In addition, Lord et al (1996) have demonstrated that training programs (aerobic, balance, and strengthening) have been proven successful at translating lower extremity muscle strength increases into improvement in gait in older adults.…”
Section: ) Graduate School Of Physical Education National Institutementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exercise on lower extremity muscle strength and these age-related gait changes have been reported for adults aged 60 years and older (Buchner et al, 1997;Lord et al, 1996). In addition, Lord et al (1996) have demonstrated that training programs (aerobic, balance, and strengthening) have been proven successful at translating lower extremity muscle strength increases into improvement in gait in older adults.…”
Section: ) Graduate School Of Physical Education National Institutementioning
confidence: 99%
“…In addition, Lord et al (1996) have demonstrated that training programs (aerobic, balance, and strengthening) have been proven successful at translating lower extremity muscle strength increases into improvement in gait in older adults. A limitation to previous work has been the selection of only one dependent measure, the gait velocity test, to assess the effectiveness of the exercise intervention.…”
Section: ) Graduate School Of Physical Education National Institutementioning
confidence: 99%
“…Assim, no idoso, é necessário que o fortalecimento muscular seja feito em alta intensidade. Alguns estudos com fortalecimento de baixa intensidade resultaram em aumento da força muscular (11,47) , porém, com ausência ou efeito muito baixo na saúde do idoso (48,49) . Apesar de o fortalecimento muscular levar a melhora da função, outros exercícios mais funcionais são necessários para haver ganho maior no equilíbrio e na independência do idoso (11,12) .…”
Section: Benefícios Da Atividade Física Para a População Idosaunclassified
“…Alguns estudos com fortalecimento de baixa intensidade resultaram em aumento da força muscular (11,47) , porém, com ausência ou efeito muito baixo na saúde do idoso (48,49) . Apesar de o fortalecimento muscular levar a melhora da função, outros exercícios mais funcionais são necessários para haver ganho maior no equilíbrio e na independência do idoso (11,12) . Orr et al (50) realizaram uma revisão sistemática que avaliou a eficácia do fortalecimento muscular progressivo sobre o equilíbrio corporal e sugerem que esse tipo de treinamento realizado isoladamente não é efetivo para a melhora do equilíbrio, acrescentando que outros fatores estão envolvidos na estabilidade postural.…”
Section: Benefícios Da Atividade Física Para a População Idosaunclassified
See 1 more Smart Citation